Roman Virtues in the Christian Context of St Augustine’s De Civitate Dei - I. N. Buzykina (Концепт: философия, религия, культура, 2020)
The topic of this paper is the continuity of major religious, moral and ethical concepts of Roman culture in following periods. These are the virtues of the citizen, namely virtus, fides and pietas — which distinguish the Roman citizen as a brave warrior, honest magistrate and pious pater familias. The central one was the duty to the City. Some traces of this tradition can be observed in the most influental sources of the Christian Patristic period, although the very intention of morals has changed: res publica, a common/communal duty, was replaced by the adoration of God. With the view to a representative research, De Civitate Dei by Saint Augustine, the most famous Christian treatise dealing with the state, civic rights, state religion, authority etc. was analyzed. On the one hand, this great book provides multiple suitable illustrations for almost every feature of the continuity between the Ancient pagan culture and Christian intellectual one. On the other hand, it isn’t just a plain comparison of loci classici in pagan and Christian context, one can find the origins of a completely new approach to the world history, which had had an influence on minds of further generations of Christian theologians in Middle Ages and later periods.